Constructive anarchy : building infrastructures of resistance - Shantz, Jeff (Ashgate Pub. Co., 2010)
Constructive Anarchy draws on over a decade of direct study within a variety of anarchist projects to provide the most wide-ranging and detailed analysis of current anarchist endeavours to date. The book offers compelling discussions of anarchism and union organizing, anti-poverty work and immigrant and refugee defence, and is a groundbreaking achievement from one of the rising scholars of contemporary anarchism.